Pengaruh E-Service dan E-Trust Terhadap Repurchase Intention Pada Ryn Boutique Medan - Mayzira, Chantika; Sahir, Syafrida Hafni (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This study aims to determine the Effect of E-Service Quality and E-Trust on Repurchase Intention at Ryn Boutique Medan. This type of research is associative with a quantitative approach. The data used are primary data or questionnaires, with data collection techniques through direct surveys to customers. The data analysis method uses SPSS 25 to test the hypothesis. The population in this study were all Ryn Boutique Medan customers totaling 150 consumers. The sampling technique used was probability sampling, and with the Slovin formula, the number of samples in this study was 100 respondents. Data testing was carried out through multiple linear regression analysis. Based on the results of this study, partially the Effect of E-Service Quality (X1) has a positive and significant effect on Repurchase Intention at Ryn Boutique Medan. The Effect of E-Trust (X2) also has a positive and significant effect. So it can be concluded that E-Service Quality and E-Trust have a positive and significant effect on Repurchase Intention at Ryn Boutique Medan.